REMITANSI PASSOMPE TERHADAP KEHIDUPAN MASYARAKAT (STUDI KASUS DI JAMPUE, KELURAHAN LANRISANG, KECAMATAN LANRISANG, KABUPATEN PINRANG) - Arafah; Muhammad Syukur; St. Junaeda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the passompe remittances on people's lives (case study in Jampue, Lanrisang Village, Lanrisang District, Pinrang Regency). This research is descriptive research using a qualitative approach through observation, interviews and document methods. The research results show that 1). Passompe motivation in Jampue to Malaysia is influenced by 3 factors, namely; first, push factors (not fulfilling the economic demands of life, being the backbone of the family and stress and other related things due to easier access to transportation as well as passompe success stories) second, pull factors (presence of relatives in Malaysia, job opportunities available, housing facilities available , income in accordance with the results of work, easy qualification requirements, comfortable environment and available educational facilities) and third, obstacles that hinder factors (lack of adventurousness and willingness to manage a business in the village). 2). Passompe remittances in Jampue provide 2 benefits, namely; first, for the passompe & passompe family (for the daily needs of the passompe and the family left behind, expenses for holidays such as Eid & weddings, supporting children's education and future investments such as building a house, buying land, opening a business, buying a vehicle & savings in the bank ) and secondly, towards the community (for building mosques, getting souvenirs and joining in celebrating big holidays such as eid & weddings).